The Incidence and Related Risk Factors of Chronic Thromboembolic Pulmonary Hypertension after Acute Pulmonary Embolism - Tosun, Halil; Kirkil, Gamze; Deveci, Figen; Dagli, Necati; Ozcan, Mete; Telo, Selda (Bilimsel Tip Publishing House, 2016)
OBJECTIVES: More than half of (>50%) the patients with choronic thromboembolic pulmonary hypertension (CTEPH) have no acute pulmonary embolism history with clinical signs, so determining the actual incidence and prevalence of CTEPH is difficult. This study aimed to investigate the incidence of CTEPH and the risk factors that may be associated with CTEPH in patients with acute pulmonary thromboembolism (PTE). MATERIAL AND METHODS: Three hundred and eighteen patients with acute pulmonary embolism diagnosed by thorax CT or ventilation/perfussion scintigraphy in our clinic were included into this study. Patients with risk factors for pulmonary hypertension other than thromboembolic disease were excluded from the study. Patients with pulmonary hypertension (PHT) (systolic PAB > 35 mmHg) determined by echocardiography performed in the 6th month were enrolled into the study. RESULTS: Fifty-seven of the 112 patients were female, and the mean age was 57.09 +/- 17.30 (16-86) years. Presence of PHT was determined in the 6th month in 45 of the 112 patients (8 of them were symptomatic) and CTEPH incidence (symptomatic + asymptomatic) was identified as 40.16%. Symptomatic CTEPH incidence was calculated as 7.14%. When we searched about the risk factors that may have a role in the development of CTEPH; we determined that CTEPH risk was increased 4.59 times by only being male (95% CI 1.071-19.683, p=0.040), 218 times by previous history of DVT (95% CI 1.235-38543.073, p=0.041), and 56.903 times by PaO2 < 80 mmHg (95% CI 2.656-1219.228, p=0.010). CONCLUSION: CTEPH development after PTE is a situation that can occur in many patients. If probable risk factors are known, patients can be closely monitorized for CTEPH development.
Keywords: Pulmonary thromboembolism; chronic thromboembolic pulmonary hypertension; incidence; risk factors